ANALISIS DAMPAK PELECEHAN SEKSUAL TERHADAP KORBAN PELECEHAN SEKSUAL DI KECAMATAN KAMANG BARU KABUPATEN SIJUJUNG - Novrita, Palda; Rahmi Sari Kasoema (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The prevalence of sexual violence in Indonesia remains a serious issue. According to data from the Online Information System for the Protection of Women and Children initiated by the Ministry of Women's Empowerment and Child Protection in 2022, there were 11,686 reported cases of sexual violence. The purpose of this research is to analyze the impacts that arise in victims of sexual harassment in Kamang Baru sub-district. This research is a qualitative study with a total of 3 teenage informants and 3 parents of 3 teenage victims of sexual harassment. This research was conducted in Kamang Baru sub-district, Sijunjung district, in 2024-2025.The results of the study state that the sexual harassment experienced by the victims greatly affects several important aspects of the victims' lives, namely their psychological, social, and cognitive well-being. The parents also confirmed that the impacts mentioned by the researcher after the incident of sexual harassment experienced by their children, such as psychological disorders, introversion, and decreased desire to learn, are indeed present in their children.The role of parents here is only to always support their children and remind them to be more cautious about the outside world. From the research results, the researcher can conclude that the impact of sexual harassment on the victims is very disturbing and even causes prolonged trauma in the victims, as well as greatly affecting their cognitive abilities and fear of socializing with the outside world.The suggestion from this research is that it can open the reader's insight into the impacts that will arise in victims of sexual harassment.